2012
DOI: 10.1128/jvi.01767-12
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Two Helicobacter pylori Bacteriophages Isolated from Japanese Patients

Abstract: Helicobacter pylori causes peptic ulcers and gastric cancer, which lead to significantly higher morbidity in Japan than elsewhere in the world. As bacteriophage (phage) and host bacteria coevolve, the study of H. pylori phages is important to extend understanding of the evolution and pathogenesis of H. pylori. Here we report two complete genome sequences of H. pylori phages KHP30 and KHP40, which were released spontaneously from the most pathogenic East Asian-type isolates from Japanese patients. Helicobacter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 13 publications
2
40
0
2
Order By: Relevance
“…Phage KHP30 has a double-stranded DNA (dsDNA) genome (16). Spherical phages with dsDNA often contain lipids inside the phage particles (53), and so they seemed to have a smaller genomic DNA size relative to the particle volume than the tailed phages.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phage KHP30 has a double-stranded DNA (dsDNA) genome (16). Spherical phages with dsDNA often contain lipids inside the phage particles (53), and so they seemed to have a smaller genomic DNA size relative to the particle volume than the tailed phages.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently isolated phage KHP30 from the culture supernatant of an East Asian H. pylori strain, NY43, isolated from a patient at Yamaguchi University Hospital in Japan, and have reported its genomic sequence (16). To extend our understanding of the contribution of phages to H. pylori evolution, the biological characteristics of the H. pylori phages must be examined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This diversity can be attributed to altered DNA repair, elevated mutation rates, high frequency of intraspecific recombination, chromosomal DNA transfer events from other species, incorporation of naked DNA from the environment, plasmid mobilization, and integration of acquired DNA in the so-called plasticity zones [4,[8][9][10]. In addition, the presence of phages has been described for several H. pylori strains, acting as another source of bacterial diversity and evolution [11][12][13][14][15]. Using newly developed bioinformatics programs, recent comparative studies of 29 complete genome sequences of strains from different parts of the world revealed a high-resolution picture of the H. pylori population structure as well as the extent and direction of genetic flux between subgroups of the bacterium [16].…”
Section: Introductionmentioning
confidence: 99%